1980 : America's Pivotal Year - Cullen, Jim, 1962- (Book collections on Project MUSE., 2023)
"1980 was a turning point in American history. When the year began, it was still very much the 1970s, with Jimmy Carter in the White House, a sluggish economy marked by high inflation, and the disco still riding the airwaves. When it ended, Ronald Reagan won the presidency in a landslide, inaugurating a rightward turn in American politics and culture. We still feel the effects of this tectonic shift today, as even subsequent Democratic administrations have offered neoliberal economic and social policies that owe more to Reagan than to FDR or LBJ. To understand what the American public was thinking during this pivotal year, we need to examine what they were reading, listening to, and watching. 1980: American Culture in Transition puts the news events of the era-everything from the Iran hostage crisis to the rise of televangelism-into conversation with the year's popular culture. Separate chapters focus on the movies, television shows, songs, and books that Americans were talking about that year, including both the biggest hits and some notable flops that failed to capture the shifting zeitgeist. As he looks at the events that had Americans glued to their screens, from the Miracle on Ice to the mystery of Who Shot JR, cultural historian Jim Cullen garners surprising insights about how Americans' attitudes were changing as they entered the 1980s"--